The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1038/leu.2017.112
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloproliferative leukemia protein activation directly induces fibrocyte differentiation to cause myelofibrosis

Abstract: Myelofibrosis (MF) may be caused by various pathogenic mechanisms such as elevation in circulating cytokine levels, cellular interactions and genetic mutations. However, the underlying mechanism of MF still remains unknown. Recent studies have revealed that fibrocytes, the spindle-shaped fibroblast-like hematopoietic cells, and the thrombopoietin (TPO)/myeloproliferative leukemia protein (MPL; TPO receptor) signaling pathway play a certain role in the development of MF. In the present study, we aimed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Our analysis would suggest that, based on interaction with hematopoietic progenitors, CD8 T cells are more active in patients with PMF. This is in line with the clinical observation that hematopoietic progenitors could respond to chronic inflammation in the context of a systemic autoimmune disease favoring fibroblast activation leading to bone marrow fibrosis and progressive cytopenias, in both primary and secondary myelofibrosis [63]. Moreover, we found that HLA class I genes expression levels were closely related to PMF disease and JAK2 V617F mutation, indicating a potential relationship with CD8 + T-cells [64].…”
Section: Discussionsupporting
confidence: 89%
“…Our analysis would suggest that, based on interaction with hematopoietic progenitors, CD8 T cells are more active in patients with PMF. This is in line with the clinical observation that hematopoietic progenitors could respond to chronic inflammation in the context of a systemic autoimmune disease favoring fibroblast activation leading to bone marrow fibrosis and progressive cytopenias, in both primary and secondary myelofibrosis [63]. Moreover, we found that HLA class I genes expression levels were closely related to PMF disease and JAK2 V617F mutation, indicating a potential relationship with CD8 + T-cells [64].…”
Section: Discussionsupporting
confidence: 89%
“…As expected, stimulation of mu/hu MPL with TPO abolished the differences in STAT5 activation in presence of any of the CALR mutants and CALR wt. In order to verify whether the mild MF phenotype developed by del52/del52 KI mice was due to sub-optimal stimulation of mu MPL by the chim CALR del52 protein, we treated 1 month post-induction homozygous KI mice with the MPL agonist romiplostim, that was previously reported to induce MF in wt mice 15 . The romiplostim-treated homozygous del52 KI mice developed a significant BM hypocellularity and splenomegaly compared to treated wt littermates ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…82 Prospective data on the effects of dose interruptions, the optimal duration of the interruptions, and the efficacy and optimal dosing of TPO mimetics are lacking. Potential financial restrictions and the risks of thrombosis and myelofibrosis 95,96 should also be considered with these agents. TPO agonists require a minimum of 5 days to boost platelet production and reach maximum efficacy at w12 days.…”
Section: Cytopeniasmentioning
confidence: 99%